Übermäßiges Körpergewicht und Krebsrisiko - Scherübl, Hans (DMW - Deutsche Medizinische Wochenschrift, 2020)
Excess body weight (EBW) is the second most important and potentially modifiable risk factor of cancer in Germany. The longer and the more excess body weight a person has, the higher the cancer risk. About 60 % of adult Germans have EBW (BMI ≥ 25.0 kg/m²) and more than 23 % are obese (BMI ≥ 30.0 kg/m²). Excess body weight is causally associated with colorectal, esophageal (adenocarcinoma), gastric (cardia), pancreatic, biliary, hepatocellular, kidney, thyroid, breast (postmenopausal), endometrial and ovarian cancer as well as multiple myeloma and meningioma. In recent years, more and more young adults (20–40 years) were diagnosed with EBW-associated tumors. People with EBW should be encouraged to join programs of cancer screening. Keeping a healthy weight is a major public health concern in Germany.
Keywords: Darmkrebs; Ösophaguskarzinom; Magentumor; Pankreasneoplasie; Leberkrebs; Übergewicht; Adipositas